Five‐year retrospective study on success, survival and incidence of complications of single crowns supported by dental implants. Issue 5 (22nd June 2016) - Tey, Valerie H. S.; Phillips, Rachel; Tan, Ken
Abstract: Objective: To determine the survival and the incidence of biologic and technical complications of implant‐supported single crowns after 5 years of function. Material and methods: Patients treated with dental implants at the National Dental Centre, Singapore, from 2006 to 2010 were recruited from the Implant Registry and evaluated by two clinicians. One hundred and ninety‐four patients, with 266 implant single crowns (SCs), were examined clinically for biologic and technical parameters. Digital radiographs were also obtained. Failure and complication rates were calculated based on the person‐time at risk. Results: The mean biologic time in function was 5.9 ± 1.3 years. None of the implants had been lost, resulting in a 5‐year survival of 100%. The corresponding success (complication‐free) rate was 92.9% (95% CI: 89.2, 95.4). The mean prosthetic time in function was 5.2 ± 1.5 years, with a 5‐year survival of implant‐supported SCs of 98.2% (95% CI: 95.8, 99.3). The corresponding success rate was 88.9% (95% CI: 84.8, 92.0). The 5‐year incidence of biologic complications, defined as PPD ≥6 mm with bleeding on probing/suppuration, in the presence of ≥2.5 mm of radiographic bone loss, was 7.1% (95% CI: 4.6, 10.9). The 5‐year incidence of technical complications was 6.5% (95% CI: 3.9, 10.7) for fracture of the veneering material, 4.3% (95% CI: 2.4, 7.7) for loss of retention, 2.1% (95% CI: 1.0, 4.7) for abutment screw loosening and 0.4% (95% CI: 0.1, 2.5) for abutment fracture. Conclusions: High survival rates (98.4%) for both the single tooth implants and the respective single crowns were demonstrated after 5.2 ± 1.5 years. However, the success rates were considerably lower (84.9%), indicating that biologic and technical complications were frequent.